Determining the efficacy and safety of acupuncture for the treatment of menstrual migraine: an updated systematic review and meta-analysis - Wu, Qiqi; Fan, Lijuan; Wu, Danhui; Gao, Hong; Han, Dexiong; Hu, Hantong; Qian, Lala (Frontiers in Neurology, 2025)
BackgroundMenstrual migraine (MM) is a common type of headache linked to hormonal fluctuations during the menstrual cycle, remains challenging to treat due to the limited efficacy of current therapies. While acupuncture shows potential as a therapeutic option for MM, the existing evidence does not clearly support its routine clinical use. This protocol for a systematic review (SR) and meta-analysis seeks to gather and evaluate recent clinical evidence regarding the effectiveness and safety of acupuncture in treating MM.MethodsA comprehensive search was conducted across multiple databases from their inception to April 2025, including PubMed, Medline, Ovid, Embase, ScienceDirect, the Chinese National Knowledge Infrastructure (CNKI), Wanfang, the Chinese Biomedical Literature (CBM) database, and the VIP Database. This was complemented by regular updates from trial registries such as the Cochrane Central Register of Controlled Trials (CENTRAL) and the WHO International Clinical Trials Registry Platform (ICTRP), which target unpublished and ongoing randomized controlled trials (RCTs). Eligible studies were RCTs comparing acupuncture with Western medicine, herbal remedies, sham acupuncture, or no intervention for the management of MM. Primary outcomes included the pain intensity [Visual Analog Scale (VAS)], the frequency of migraine attacks (FM), and duration of migraine (DM). Secondary outcomes encompassed response rate, Headache Impact Test-6 (HIT-6), the Menstrual Headache Index (MHI), the serum levels of 5-hydroxytryptamine (5-HT), and adverse events. Analyses involved meta-analysis, subgroup comparisons, publication bias detection, sensitivity testing, risk-of-bias evaluations, and profiling of adverse events. The quality of evidence was judged according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) criteria.ResultsA total of 39 RCTs comprising 2,584 participants were included. Compared with control interventions, acupuncture significantly reduced VAS scores, decreased the frequency and duration of migraine attacks, and improved response rates, as well as HIT-6 and MHI scores. Additionally, acupuncture was associated with increased serum 5-HT levels. Meta-analytic findings indicated that acupuncture demonstrated a favorable safety profile in the treatment of MM.ConclusionFindings suggest that acupuncture for MM produced the most notable reductions in migraine severity. Nevertheless, the GRADE assessment indicated low overall certainty of the evidence, with considerable heterogeneity present in multiple pooled analyses. Therefore, well-designed, large-scale RCTs are urgently required to strengthen the evidence base.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022367446.